A trichromatic MOF composite for multidimensional ratiometric luminescent sensing - Zhao, He; Ni, Jun; Zhang, Jian-Jun; Liu, Shu-Qin; Sun, Ying-Ji; Zhou, Huajun; Li, Yan-Qin; Duan, Chun-Ying (Chemical science (Cambridge), 2018)
Low-cost, high-performance luminescent probes with wide application potential have been actively pursued. Conventional luminescent probes, which rely on single or dual emissions responsive to analyte molecules, demonstrate limited sensitivity and selectivity because the single emissions can be easily affected by many non-analyte factors, while the dual emissions can only offer single-ratiometric luminescent sensing. Here we report a white-light-emitting trichromatic MOF composite ( W2 ) as the first multidimensional ratiometric luminescent probe. It is facilely synthesized by simultaneously incorporating red- and green-emitting iridium and ruthenium complex cations as encapsulated luminescent modules (ELMs) into a porous blue-emitting MOF via ion exchange. Specific volatile organic solvents (VOSs) can cause VOS-dependent changes to the MOF-to-ELM energy transfer efficiencies in W2 , while nitroaromatic (NAC) vapors intriguingly and unprecedentedly quench the three emissions at different rates, both of which enable visible luminescent sensing. Each VOS can be correlated to a unique combination of the two MOF-to-ELM ratios of emission-peak heights, enabling a two-dimensional (2D) code recognition. Furthermore, the time-dependent evolution of the two ratios upon exposure to selective NAC vapors can be mapped out, achieving the first 3D code recognition. Both the synthetic and sensing strategies can be further implemented to develop low-cost and effective luminescent probes. A trichromatic MOF composite utilizes its MOF matrix and two encapsulated cations collectively to achieve unprecedented multi-dimensional ratiometric luminescent sensing with high selectivity and sensitivity.